2005
DOI: 10.1590/s1519-38292005000400010
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da mortalidade de recém-nascidos internados na UTI neonatal do Hospital Geral de Caxias do Sul, Rio Grande do Sul

Abstract: Objectives: to determine causes and variables related to newborn deaths of a neonate intensive care unite (ICU) in the Southern

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
10
1
40

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 12 publications
5
10
1
40
Order By: Relevance
“…It is emphasized that similar outcomes were found in other studies, which identified a mean length of stay of 19 days. 14,24 Another study found the neonates' mean length of stay in the NICU was 14 days, and of 20 days among those who survived, 14 which agrees with the present study, considering that the mean length of stay of surviving newborns at the NICU of the referred institution was 20.1 days.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It is emphasized that similar outcomes were found in other studies, which identified a mean length of stay of 19 days. 14,24 Another study found the neonates' mean length of stay in the NICU was 14 days, and of 20 days among those who survived, 14 which agrees with the present study, considering that the mean length of stay of surviving newborns at the NICU of the referred institution was 20.1 days.…”
Section: Discussionsupporting
confidence: 91%
“…13 The mortality rate found in the present study is also greater that the 8.2% rate registered in 2005 in Caxias do Sul, a city also located in Southern Brazil. 14 It is emphasized that the studied NICU is a referral center for the mid-western macroregion of RS, and is often overcrowded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Na Tabela 1, será exposto o motivo da internação do RN na UTIN. 10 A idade gestacional e o baixo peso ao nascer determinam os prognósticos da prematuridade, devido à relevância na maturidade de vários sistemas em recém-nascido prematuros. 11 Assim, a prematuridade é uma adversidade devido às altas taxas de mortalidade e pelos riscos que pode acarretar no desenvolvimento dos recém-nascidos.…”
Section: Resultsunclassified
“…15 Salienta-se que o aumento no número de consultas pré-natais está diretamente relacionado, com a diminuição do retardo no crescimento intrauterino, prematuridade, baixo peso e óbito por essas causas. 10 Nesse sentido, ressalta-se a importância da realização de exames de urina durante a gestação, pois a infecção do trato urinário na gestante é uma forte predisposição para o parto prematuro e morbidades para o RN. 16 Um maior número de consultas no pré-natal funciona como fator protetor para o óbito neonatal, indicando a importância dos cuidados durante a gestação.…”
Section: Resultsunclassified